Analisis Algoritma Link-State yang digunakan pada Protokol Routing Is-Is dan OSPF - Robbi, Sabbiisma; Diansyah, Tengku Mohd (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the link-state algorithm implemented in two interior routing protocols, OSPF (Open Shortest Path First) and IS-IS (Intermediate System to Intermediate System), based on Quality of Service (QoS) parameters and convergence time. The research uses a quantitative approach with an experimental method through network simulation using GNS3 and traffic analysis via Wireshark. A nine-router topology with area segmentation is built to evaluate the performance of each protocol under normal and failure conditions. The parameters tested include delay, jitter, throughput, packet loss, hop count, routing cost, and convergence time. The results indicate that IS-IS tends to provide more stable delay and routing cost across areas, while OSPF performs better in convergence speed. Therefore, selecting the appropriate routing protocol depends on the network’s preference between stability and recovery speed.